Analysis and Synthesis for Interval Type-2 Fuzzy-Model-Based Systems - Li, Hongyi; Wu, Ligang; Lam, Hak-Keung; Gao, Yabin (Springer Nature Singapore : Imprint: Springer, 2016)
This book develops a set of reference methods capable of modeling uncertainties existing in membership functions, and analyzing and synthesizing the interval type-2 fuzzy systems with desired performances. It also provides numerous simulation results for various examples, which fill certain gaps in this area of research and may serve as benchmark solutions for the readers. Interval type-2 T-S fuzzy models provide a convenient and flexible method for analysis and synthesis of complex nonlinear systems with uncertainties.